Quality Management of Teaching and Non-Teaching Staff at PPTQ Ummul Qur’an Sukoharjo - Rakhmad Agung Hidayatullah; Joko Ariyanto; Nanang Dwi Purwanto; Radar Madani Al Islami (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
This study aims to examine in depth the management of teaching and educational staff at Pondok Pesantren Tahfizhul Qur’an (PPTQ) Ummul Qur’an Sukoharjo, focusing on the aspects of planning, organizing, implementation, evaluation, and the challenges encountered in supporting the achievement of Qur’anic memorization education. This study is grounded in the urgency of human resource management in pesantren, which requires the integration of pedagogical competence, Qur’anic memorization ability, and caregiving functions. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with pesantren leaders and teaching staff, field observations of learning and caregiving activities, and documentation of relevant institutional records. Data analysis was conducted thematically through data reduction, data display, and conclusion drawing. The findings indicate that the management of teaching and educational staff at PPTQ Ummul Qur’an has functioned effectively through a familial approach, with musyrif playing a central role as educators, caregivers, and role models for students in the tahfizh learning process. However, the study also reveals limitations in the performance evaluation system, which has not yet been structured systematically, as well as the lack of sustainable professional development programs for teaching staff. This research is limited to a single pesantren, and therefore the findings cannot be generalized to all tahfizh pesantren. Nevertheless, the results provide practical implications for pesantren administrators in developing more structured management systems for teaching staff without neglecting the distinctive values of pesantren. This study offers original value by enriching the literature on Islamic education management through an integrative approach that combines modern management principles with pesantren caregiving values